2003
DOI: 10.2169/internalmedicine.42.336
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Malignant Lymphoma in the Right Atrium after Systemic Chemotherapy

Abstract: A74-year-old manwas referred to us for evaluation of a tumor in the right atrium (RA). Transesophageal echocardiography (TEE) showed an unmovable 50x60 mm mass in the RA. Based on histological findings of subcutaneous tumors in the right abdominal wall, he was diagnosed as malignant lymphoma(ML), and treated with a THP-COPregimen. Upon completion of first THO-COP therapy, TEEshowed marked regression of the mass and division into 3 masses, one of which showed marked floating movementwith a small stalk. To preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Several articles report successful treatment of primary cardiac lymphoma with chemotherapy, 5-8 while others report successful treatment by surgical resection and chemotherapy. [9][10][11] However, Ceresoli et al reported that there is no evidence of survival improvement with surgery. 5 In the present case, right heart failure deteriorated rapidly after referral.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles report successful treatment of primary cardiac lymphoma with chemotherapy, 5-8 while others report successful treatment by surgical resection and chemotherapy. [9][10][11] However, Ceresoli et al reported that there is no evidence of survival improvement with surgery. 5 In the present case, right heart failure deteriorated rapidly after referral.…”
Section: Discussionmentioning
confidence: 99%
“…23 Surgical resection of tumor may be considered only on a case by case basis. 25 For the case in discussion, surgical approach was considered but not pursued, as the patient responded very promptly to systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%